Līdzdalība noziedzīgā nodarījumā - Šmitaite, Margarita (Latvijas Universitāte, 2025)
Bakalaura darbā “Līdzdalība noziedzīgā nodarījumā” tiek analizēta līdzdalības institūta vēsturiskā attīstība Latvijas teritorijā, līdzdalības jēdziens no dažādu autoru skatpunkta. Tāpat tiek aplūkoti jautājumi par līdzdalības nošķiršanu no dalības un līdzdalības nošķiršanu no piesaistības noziedzīgā nodarījumā. Darba aktualitāti nosaka pieaugošais kolektīvo noziedzīgo nodarījumu īpatsvars un nepieciešamība pēc skaidriem kritērijiem, kas ļautu nošķirt līdzdalību no dalības un precīzi noteikt katras personas atbildības apmēru. Darba mērķis ir noskaidrot līdzdalības jēdziena būtību, tiesu praksi, kā arī noskaidrot ārvalstu pieeju līdzdalības institūta regulējuma, lai formulētu priekšlikumus regulējuma pilnveidei.

The bachelor’s thesis titled “Participation in a Criminal Offense” examines the historical development of the legal institution of participation within the territory of Latvia, as well as the concept of participation from the perspectives of various scholars. The thesis also addresses issues concerning the differentiation between participation and complicity, and the distinction between participation and involvement in a criminal offense. The relevance of the research is underscored by increasing proportion of collective criminal offenses and the pressing need for clear and precise criteria that enable the distinction between participation and complicity, thereby ensuring the accurate determination of each individual’s degree of responsibility. The primary objective of the thesis is to elucidate the essence of the concept of participation, to analyze judicial practice, and to examine foreign approaches to the regulation of the institution of participation, with the aim of formulating proposals for the improvement of the existing legal framework.
Participation in a Criminal Offense
Keywords: Juridiskā zinātne; Līdzdalība; Dalība; Izdarītājs; Organizētājs; Uzkūdītājs